Effect of pulsed electric fields (PEF) combined with natural antimicrobial by-products against S. Typhimurium. (October 2016) - Sanz-Puig, Maria; Santos-Carvalho, Leonor; Cunha, Luís Miguel; Pina-Pérez, M. Consuelo; Martínez, Antonio; Rodrigo, Dolores
Abstract: The effect against Salmonella enterica serovar Typhimurium of PEF treatment combined with cauliflower and mandarin by-product infusions at several concentrations (0, 1, 5, and 10% (w/v)) was evaluated at various incubation temperatures (10, 22, and 37 °C). The possible synergistic antimicrobial action of the combined process of Pulsed Electric Field (PEF) technology followed by exposure to the by-product infusions and the occurrence of sublethal cellular damage were also studied. Antimicrobial kinetics of by-product infusions alone or following PEF treatment were fitted to a Weibull model. Both mandarin and cauliflower by-product infusions showed a maximum antimicrobial effect against S. Typhimurium after 10 h at 37 °C when the microorganism was exposed to 10% of by-product infusion, achieving reductions of initial bacterial load up to undetectable levels. The effect of the PEF treatment (20 kV–900 μs) caused a reduction of 4 log cycles of the initial cell population (10 8  cfu/mL) of S. Typhimurium and 1 log cycle (90%) of cellular damage. Moreover, when the PEF pre-treated S. Typhimurium population was subjected to subsequent incubation in the presence of both by-product [10%] infusions, the microbial inactivation was faster, achieving a reduction of the initial bacterial load (4 log10  cycles) up to undetectable levels in 2 h. The kinetic values of the Weibull model were obtained. The higher the concentration of by-product infusion, temperature, and PEF treatment applied, the greater the kinetic parameter "b" values, which are related to the microbial inactivation rate. Therefore, the addition of cauliflower and mandarin by-product infusions could be a good additional control measure contributing to ensure bacterial counts below recommended limits in pasteurized PEF products during their storage at refrigeration temperatures. Highlights: The effect of PEF and by-product infusions was evaluated against S. Typhimurium. Cauliflower and mandarin by-product infusions had a substantial antimicrobial effect. Combining PEF treatment with exposure to infusions had a synergistic effect. Weibull b values were higher when combined treatment was applied.